2010
DOI: 10.1166/jnn.2010.2446
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of the Isolated Straight Polymer Chain Inside of Single-Walled Carbon Nanotubes

Abstract: In this paper, a novel molecular wire comprising an isolated straight polystyrene (PS) chain encapsulated by a single-walled carbon nantube (SWNT) was prepared. The interaction of the PS chain with the SWNTs was systematically characterized using transmission electron microscopy (TEM), Fourier transform infrared (FTIR) spectroscopy, nuclear magnetic resonance (NMR) spectroscopy, and Raman spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Crystallization inside CNTs has previously been observed using High-Resolution Transmission Electron Microscopy for molecules that cluster together through strong intermolecular interactions; such as inorganic crystals [45][46][47] and small organic molecules with highly conjugated moieties 48,49 . Although the encapsulation of PS inside CNTs has also been visualized by High-Resolution Transmission Electron Microscopy 50 , the crystalline PS arrangement has not been reported yet. We hypothesize that this is due to a current limitation of the experimental method, as electron beams transfer kinetic energy to the flexible polymers 51 , displacing any polymer ordering from equilibrium positions into a melted chain.…”
Section: Crystal Formationmentioning
confidence: 99%
“…Crystallization inside CNTs has previously been observed using High-Resolution Transmission Electron Microscopy for molecules that cluster together through strong intermolecular interactions; such as inorganic crystals [45][46][47] and small organic molecules with highly conjugated moieties 48,49 . Although the encapsulation of PS inside CNTs has also been visualized by High-Resolution Transmission Electron Microscopy 50 , the crystalline PS arrangement has not been reported yet. We hypothesize that this is due to a current limitation of the experimental method, as electron beams transfer kinetic energy to the flexible polymers 51 , displacing any polymer ordering from equilibrium positions into a melted chain.…”
Section: Crystal Formationmentioning
confidence: 99%
“…[2][3] Carbon nanofibers (CNFs) and carbon nanotubes (CNTs) have been extensively studied and applied as fillers for improving various properties of polymers due to their excellent mechanical, electrical and thermal properties. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] CNFs are currently being produced in volume and are significantly less expensive fillers when compared to CNTs. [23][24] Hammel et al found that CNFs are more * Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%